Chinese consumers' purchasing motivation of luxury products online - Liu, Xinyu; Stříteský, Václav; Kottika, Efthymia, 1982-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The main goal of this thesis is to find out the motivations of Chinese consumers to buy luxury products online. In order to achieve this goal, the essential attributes of luxury products as compared to ordinary products are fundamentally studied based on consumers' perceptions of luxury goods. Furthermore, the thesis investigates the development of e-commerce in the Chinese market, as well as the impact of this development on Chinese consumers and businesses, to gain a better understanding of the intentions and motivations of Chinese consumers who purchase luxury products online. Therefore, the methodology is conducted by adopting in-depth interviews with 15 Chinese luxury consumers as interviewees, while 26 questions are created as open-ended questions for the interview. As the result, Chinese consumers' motivations for buying luxury goods online vary from person to person for four core reasons: "Time-efficient", "nice packaging of the products", "Various products options", and "lower price". Meanwhile, some risks may lead to the leakage of consumers' personal information or even more severe financial loss, even with the rapid development of e-commerce. However, the advantages of online luxury goods still outweigh the disadvantages, and they also put forward their solutions to the corresponding risks. Finally, luxury brands could also benefit from the outcome of this thesis by understanding the existing problems and risks in the industry to improve according to the actual needs of luxury consumers, thus stabilizing existing customers and attracting new customers.
Vedoucí práce: Václav Stříteský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses